Pengembangan Media Pembelajaran Berbasis Android Mobile Application Pada Pekerjaan Dasar Otomotif: Pengembangan Media Pembelajaran Berbasis Android Mobile Application Pada Pekerjaan Dasar Otomotif - yoga bagus pratama; Nurcholish Arifin Handoyono; Sigit Purnomo (JURNAL VOKASI DEWANTARA (JVD), 2022)
This study aims to develop and determine the feasibility of learning media based on Android Mobile Application in the Automotive Basic Work Mapel in class X TBSM SMK Muhammadiyah 1 Wonosari. This research is research and development. The subjects in this study were media experts, materials and students of SMK 1 Muhammadiyah Wonosari with the object of Learning Media. In data collection techniques using structured interviews with a questionnaire instrument (questionnaire) type Rating Scale. While the data analysis using descriptive quantitative techniques. The results showed that the assessment of the material expert respondents obtained a score of 3,1 which was included in the appropriate category. Then based on the assessment of media experts, it obtained a score of 3,87 which was included in the very feasible category. In the assessment of small-scale product trials, the results of 3,12 are included in the very feasible category. Furthermore, in the large-scale use trial, the results of 3,04 were included in the feasible category. The conclusion of the research is the development of learning media based on android mobile application is suitable for student learning.